Dieta de Mazama temama (Kerr 1792, Artiodactyla: Cervidae) en Parque Nacional Cañón del Río Blanco Diet of Mazama temama (Kerr 1792, Artiodactyla: Cervidae) in Parque Nacional Cañón del Río Blanco - Serna-Lagunes, Ricardo; Ramos-Quechulpa, Lizbeth; Mora-Collado, Norma; Salazar-Ortiz, Juan; Ocaña-Parada, Carlos de Jesús; Gastelum-Mendoza, Fernando Isaac (Ecosistemas y Recursos Agropecuarios, 2024)
Determining the diet of herbivores through the epidermal structures present in their excreta makes it possible to identify the plants consumed and estimate the variations at different times of the year. The objective of the study was to determine the botanical composition of the diet of the deer Central American Red Brocket (Mazama temama), in the Parque Nacional Cañón del Río Blanco (PNCRB), Veracruz, Mexico. The vegetation where the study was carried out is an evergreen tropical forest with the presence of induced vegetation. Sampling was carried out during the dry and rainy season of 2021. The plant species consumed were identified with the microhistological analysis of epidermal residues in fecal samples. The diet consisted of 18 species of plants belonging to 14 botanical families. The highest percentage of consumption was for the Solanaceae family (16.6%), followed by Arecaceae, Asteraceae, Cucurbitacea and Malvaceae (11.1% each). 66% of the plants were consumed in the dry season, and consumption increased by 34% during the rainy season, showing 100% of the plant species in the rainy season, showing 100% consumption in the rainy season.. The plants consumed were 10 herbaceous plants (55.5%), six arboreal plants (33.5%), one shrub and one grass (5.5% each); forest edge plants (BB = 44%), forest interior plants (IB = 33%) and cultured plants (CP = 23%), constituted the diet. M. temama adapted its diet to the availability and temporal and spatial distribution of plants in the habitat and based on climatic conditions (dry vs. rainy).
Keywords: Agroecosystems; Natural protected areas; Microhistology technique; Cervid; Central American Red Brocket